Strategi Pengembangan Pariwisata Berkelanjutan di Desa Wisata Simamora, Kabupaten Humbang Hasundutan - Beatrice Jennifer Simamora; Dewi Yanti; Muhammad Khadry (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze sustainable tourism development strategies in Simamora Tourism Village, Humbang Hasundutan Regency. This village has significant potential in the natural and cultural tourism sector, such as Sisingamangaraja Palace, Aek Silang whitewater rafting, and Batu Nganga. However, the management of this potential has not been optimally implemented. Several challenges remain, such as low community participation, limited infrastructure, and residents' limited understanding of the concept of sustainable tourism. This study used a qualitative approach with in-depth interviews and field observations. Informants in the study included village officials, local communities, and managers of Village-Owned Enterprises (BUMDes). The data obtained were analyzed using the SOAR (Strengths, Opportunities, Aspirations, Results) approach to identify strengths, opportunities, aspirations, and expected outcomes in sustainable tourism development. The results show that although the tourism potential in Simamora Village is quite high, the lack of coordination between stakeholders and the absence of an integrated development strategy are the main obstacles. Therefore, this study recommends several strategic steps, including improving the quality of human resources in the tourism sector, strengthening supporting infrastructure, and developing tourism products based on local wisdom that can foster active community involvement. Community participation in every stage of planning and management is crucial for achieving sustainable and competitive tourism. The results of this study are expected to serve as a reference in formulating policies for sustainable village tourism development.